2019
DOI: 10.1186/s12889-019-6634-3
|View full text |Cite
|
Sign up to set email alerts
|

Community, system and policy level drivers of bovine tuberculosis in smallholder periurban dairy farms in India: a qualitative enquiry

Abstract: BackgroundRapid urbanization has led to expansion of peri-urban fringes, where intensive, industry-style livestock rearing has led to emerging vulnerabilities at the human-animal-environment interface. This study was undertaken to understand the health system and farm-level factors that influenced the risk of transmission of bovine Tuberculosis (bTB) in animals and humans in peri-urban smallholder dairy farms of India.MethodsThematic guides were developing through literature review and expert consultation. In-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…In developed countries, tuberculosis outbreaks are mitigated by strict animal control, elimination programmes and milk pasteurisation, as well as access to veterinary services, which reduces the chances of transmission to humans (Cosivi et al 1998). However, in Indian dairy farms, it has been found that selling or abandoning infected animals, lack of education about bovine tuberculosis, and only consulting veterinarians as a last resort worsens the problem (Chauhan et al 2019). As industrial food‐animal production becomes increasingly common in developing countries, agricultural intensification is likely to increase the risk of zoonotic disease emergence and spread.…”
Section: Resultsmentioning
confidence: 99%
“…In developed countries, tuberculosis outbreaks are mitigated by strict animal control, elimination programmes and milk pasteurisation, as well as access to veterinary services, which reduces the chances of transmission to humans (Cosivi et al 1998). However, in Indian dairy farms, it has been found that selling or abandoning infected animals, lack of education about bovine tuberculosis, and only consulting veterinarians as a last resort worsens the problem (Chauhan et al 2019). As industrial food‐animal production becomes increasingly common in developing countries, agricultural intensification is likely to increase the risk of zoonotic disease emergence and spread.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that while working in slaughterhouses, workers are covered in blood and cattle droppings with the potential risk of contamination (33)(34)(35)(36). The use of an apron, waterproof gloves and the wearing of a visor would limit the circumstances of accidental contact with the skin.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the authors highlighted the needs to revise the attitude and practice by the stakeholders on the occupational and public health threats of M. bovis infection including developed nations with ongoing bovine tuberculosis eradication programmes (Robinson 2019 ). A study assessing the health system, policy and dairy farm-level factors which could have impact on the zoonotic transmission have been performed in smallholder peri-urban dairy farms in India (Chauhan et al 2019 ). The study focuses on three main themes encompassing knowledge and practices related to bovine tuberculosis, limited system support for prevention and control of bovine tuberculosis and lack of effective policies and programmatic direction in the context of bovine tuberculosis.…”
Section: Tackling M Bovis Infection At Human–animmentioning
confidence: 99%
“…Furthermore, the authors also reported that the absence of effective policies and the perception of stakeholders on bovine tuberculosis remain as significant barriers in controlling bovine tuberculosis. The authors suggest that these gaps can be addressed through collaborative research and One Health approaches (Chauhan et al 2019 ).…”
Section: Tackling M Bovis Infection At Human–animmentioning
confidence: 99%